COMMODIFICATION OF CULTURAL IDENTITIES AND/OR EMPOWERMENT OF LOCAL COMMUNITIES: DEVELOPING A ROUTE OF NUCLEAR TOURISM - Mažeikienė, Natalija; Gerulaitienė, Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Research presented in the paper focuses on commodification of cultural identities and community empowerment strategies of cultural tourism in Visaginas.. One of challenges in developing tourism is orientation toward profit and commodification of culture, which becomes a problem in regard to practicing authentic identities. The article presents efforts of researchers working in the project EDUATOM to scientifically substantiate construction of new educational nuclear/ atomic tourism route in the Ignalina Nuclear Power Plant (INPP) region. The authors discuss what diverse parameters and elements of place identity could be included and represented in the tourism in Visaginas and how community empowerment and involvement of different stakeholders might contribute to practicing various commodification strategies. The article analyses commodification of cultural identities and community empowerment strategies of educational, cultural, nuclear/atomic tourism in Visaginas, using research strategy of case study, including methods of document analysis, conversations (formal and informal) with stakeholders, secondary data analysis, construction of Post-Soviet identities and empowerment of local communities.